Chicken line-dependent mortality after experimental infection with three type IIxIII recombinant Toxoplasma gondii clones - Schares, G. (2017)
Three genetically different clones of Toxoplasma gondii, also different in mouse virulence, were studied by experimental infection in chickens. For the experiments, four chicken lines were used, which differed in phylogenetic origin and performance level: two white egg layer lines, one with high laying performance (WLA), one with low (R11) and two brown layer lines, also displaying high (BLA) and low (L68) egg number. Chickens were intraperitoneally infected with three different T. gondii isolates representing type IIxIII recombinant clones, i.e. showing both, type II- and type III-specific alleles. These clones (K119/2 2C10, B136/1 B6H6, K119/2 A7) had exhibited virulence differences in a mouse model. In chickens, a significantly higher mortality was observed in white layer lines, but not in brown layer lines, suggesting that differences in the phylogenetic background may influence the susceptibility of chickens for toxoplasmosis. In addition, antibody (IgY) levels varied in surviving chickens at 31 days post infection. While low to intermediate antibody levels were observed in white layers, intermediate to high levels were measured in brown layers. Infection with a T. gondii clone showing low chicken virulence resulted in higher antibody levels in all chicken lines compared to infection with T. gondii clones of intermediate or high chicken virulence. This was in agreement with the parasite load as determined by real-time PCR. Overall, results show that progeny resulting from natural sexual recombination of T. gondii clonal lineages, may differ in their virulence for mice and chickens.